PENGEMBANGAN MODUL BAHASA ARAB BERBASIS TEORI PSIKOLOGI PERKEMBANGAN REMAJA ELIZABETH B. HURLOCK KELAS X MA - Mujab, Ahmad Saiful; Irawati, Retno Purnama; Rahmawati, Nailur (Lisanul Arab: Journal of Arabic Learning and Teaching, 2018)
The development of adolescents led to several changes, including in terms of thinking and how to learn. Adjustmentof teaching materials to students' progress will help them understand the material presented. This research designusing research and development research design (R & D). The results of this study are: 1) the number of studentswho stated that the subjects of Arabic is a difficult subject is 87.3% or a number of 42 students and 95.7% or anumber of 45 students stated that the need for development of textbooks tailored to the development the psychologyof the students of grade X Madrasah Aliyah. SWOT analysis of textbooks that have been used are books durusullughotil arabiyah and Student Worksheet "Hikmah" generate advantages, weaknesses, opportunities and threatsof both books which are then used as a basis for development of adolescent-based development module, 2) prototypemodule based on the development of adolescents written with attention to the results of SWOT analysis of textbooksthat have been used and add some things about the characteristics of adolescent development, 3) expert assessmentof the prototype of the juvenile-based module develops average grade with feasible category with details of 3.25 forthe content feasibility aspect, 3.32 for the language feasibility aspect, 3.37 for feasibility aspects of presentation, and2.95 for eligibility aspect of the maximum total score of 4. Perkembangan remaja menyebabkan beberapa perubahan, diantaranya dalam hal pemikiran dancara belajar. Penyesuaian bahan ajar dengan perkembangan siswa akan membantu mereka dalammemahami materi yang disajikan. Desain penelitian ini menggunakan desain penelitian research anddevelopment (R&D). Hasil penelitian ini yaitu: 1) jumlah siswa yang menyatakan bahwa matapelajaran bahasa Arab merupakan mata pelajaran yang sulit adalah 87,3% atau sejumlah 42 siswadan 95,7% atau sejumlah 45 siswa menyatakan bahwa perlu adanya pengembangan buku ajar yangdisesuaikan dengan perkembangan psikologi siswa Madrasah Aliyah kelas X. Analisis SWOTterhadap buku ajar yang sudah digunakan yaitu buku durusul lughotil arabiyah dan Lembar KerjaSiswa Ã¢â‚¬Å“HikmahÃ¢â‚¬Â menghasilkan kelebihan, kelemahan, peluang dan ancaman kedua buku tersebutyang selanjutnya digunakan sebagai dasar pengembangan modul berbasis perkembangan remaja, 2)prototipe modul berbasis perkembangan remaja ditulis dengan memperhatikan hasil analisis SWOTbuku ajar yang sudah digunakan serta menambahkan beberapa hal mengenai karakteristikperkembangan remaja, 3) penilaian ahli terhadap prototipe modul berbasis perkembangan remajamemperoleh rata-rata nilai dengan kategori layak dengan rincian 3,25 untuk aspek kelayakan isi,3,32 untuk aspek kelayakan bahasa, 3,37 untuk aspek kelayakan penyajian, serta 2,95 untuk aspekkelayakan kegrafikan dari skor total maksimal 4.